Tax complexities in the Malaysian corporate tax system: minimise to maximise - Isa, Khadijah (Emerald Group Publishing Limited, 2014)
Purpose – This paper aims to examine areas of tax difficulties encountered by corporate taxpayers in complying with tax obligations under the self-assessment system. Design/methodology/approach – A two-phase exploratory mixed methods approach was employed. The first phase involves eight focus group interviews with 60 tax auditors from the Inland Revenue Board of Malaysia (IRBM) and the second phase adopts a mixed-mode survey among selected Malaysian corporate taxpayers. Thematic analysis and descriptive and inferential analysis were used to examine the qualitative and quantitative data in achieving the objective. Findings – Three dimensions of tax complexity encountered by corporate taxpayers were tax computations, record keeping and tax ambiguity. The first two complexity dimensions were faced largely by smaller companies. On the other hand, the least difficult tax-related areas were dealing with tax agents, submitting tax returns within the given time and dealing with the tax authority. Practical implications – In a tax policy context, this study enables international tax authorities in general, and Malaysian tax authority in particular, to have greater confidence in developing and administering tax laws and policies to maintain and/or increase the overall level of corporate tax compliance. Originality/value – Unlike prior studies that mainly used individual taxpayers or students as research participants, this study employed corporate tax auditors from the tax authority and corporate tax officers. Tax auditors and corporate taxpayers provide invaluable insights into the possible determinants of compliance variables. These insights are based on their practical experience in handling corporate tax audits and managing corporate tax matters, respectively.